2005
DOI: 10.1007/s00125-005-1946-5
|View full text |Cite
|
Sign up to set email alerts
|

The Somogyi phenomenon revisited using continuous glucose monitoring in daily life

Abstract: In 1959, Michael Somogyi reported that hypoglycaemia during the night was often followed by heavy glycosuria next morning [1]. Moreover, a high morning fasting blood glucose value was later attributed to nocturnal hypoglycaemia and the need to reduce the evening or bedtime dose of insulin. The Somogyi phenomenon-hypoglycaemia begetting hyperglycaemia-is believed to be due to the release of counterregulatory hormones in response to (nocturnal) insulin-induced hypoglycaemia. Despite the fact that experimental st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 9 publications
(13 reference statements)
3
28
1
3
Order By: Relevance
“…He attributed this phenomenon to episodes of hypoglycemia (often undetected) that provoked release of counterregulatory hormones. Recent studies, including studies of such patients with sensitive methods that have excluded antecedent hypoglycemia as the cause, have shed doubt on his original explanation (15). We suggest that insulininduced insulin resistance is the most likely mechanism.…”
Section: Insulin Resistance Disrupts Insulinmentioning
confidence: 75%
“…He attributed this phenomenon to episodes of hypoglycemia (often undetected) that provoked release of counterregulatory hormones. Recent studies, including studies of such patients with sensitive methods that have excluded antecedent hypoglycemia as the cause, have shed doubt on his original explanation (15). We suggest that insulininduced insulin resistance is the most likely mechanism.…”
Section: Insulin Resistance Disrupts Insulinmentioning
confidence: 75%
“…In our research letter, we reported a significant difference in mean fasting morning blood glucose between nights without hypoglycaemia and the other two categories of glycaemia [5]. Similarly, we found that 1 h after measurement of fasting morning blood glucose, the mean glucose value for nights without hypoglycaemia (mean ± SEM: 11.9±0.3 mmol/l) was significantly different from that for possible hypoglycaemic nights (9.8±0.6 mmol/l, p<0.003, Bonferroni corrected) and that for hypoglycaemic nights (10.3±0.4 mmol/l, p<0.006, Bonferroni corrected).…”
mentioning
confidence: 62%
“…With the years, this phrase has been interpreted as nocturnal hypoglycaemia inducing high morning blood glucose values [4]. In our letter we rejected this clinical statement by showing that if patients have a nocturnal hypoglycaemic episode during the night there was a high probability that blood glucose the following morning was low [5]. This finding suggests that hormonal counter-regulation alone is not capable of inducing hyperglycaemic excursions in type 1 diabetic patients.…”
mentioning
confidence: 77%
“…Все ночи были разделены на 3 группы: с ночной гипогликемией (уровень глюкозы по дан-ным НМГ ниже 2,2 ммоль/л в течение как минимум 10 минут), с возможной гипогликемией (уровень глю-козы от 2,3 до 3,5 ммоль/л) и без гипогликемии (уровень глюкозы >3,5 ммоль/л) (табл. 4) [22]. Уровень глюкозы крови натощак был значительно ниже после ночи с гипогликемией или с возможной гипогликемией по сравнению с ночами без гипоглике-мий.…”
Section: последующие исследования феномена сомоджиunclassified
“…Таким образом, Т. Hoi-Hansen и соавт. заключают, что полученные данные не подтверждают существование феномена Сомоджи, и риск ночной гипогликемии посте-пенно возрастает при снижении уровня глюкозы крови натощак [22].…”
Section: последующие исследования феномена сомоджиunclassified